Digital Reading Competency of Students: A Study in Universities in Kerala - P., Divya; Haneefa, Mohamed (DESIDOC Journal of Library & Information Technology, 2018)
The purpose of this study was to gain insight into the digital reading competency of the students in universities in Kerala. Structured questionnaires were used to collect data from a representative sample of 525 students of the teaching departments of three prominent universities in Kerala. The findings revealed that a good number of the students have a medium level of digital reading competency. It is also noted that male students exhibited a high level of competency as compared with female students and also that there exists a significant relationship between digital reading competency and level of competency to use computer and other digital devices. This study will be useful to develop digital literacy education framework which will enhance student’s digital reading competency.